THE EFFECT OF SHOPPING LIFESTYLE, HEDONIC SHOPPING MOTIVATION, AND SALES PROMOTION ON IMPULSE BUYING BEHAVIOR IN E-COMMERCE (CASE STUDY OF BERRYBENKA CONSUMER) - Nia Yusnia Sari; Sri Hermawati (Jurnal Ilmiah Ekonomi Bisnis, 2020)
Increasing internet users and the growing of e-commerce in Indonesia impact on consumer behaviour in terms of shopping. One of the models of shopping channels that are currently being the world's trend is replacing conventional shopping systems that require shoppers to come to shopping with a shopping system online.  This research aims to determine whether there is a influence on shopping lifestyle, hedonic shopping motivation and sales promotion of impulse buying in Berrybenka consumer. The samples on this research are consumers who have ever shopped at Berrybenka e-commerce through websites or applications. The sampling method used in this study is non probability sampling using the purposive sampling technique. The data analysis used is a descriptive analysis and confirmatory factor analysis (CFA). The hypothesis test results show that shopping lifestyle variable affects impulse buying behavior, while hedonic shopping motivation and sales promotion have no effect on the impulse buying behavior.